Deep eutectic solvent-assisted synthesis of highly efficient PtCu alloy nanoclusters on carbon nanotubes for methanol oxidation reaction. (1st November 2019) - Zhong, Jingping; Li, Lili; Waqas, Muhammad; Wang, Xiaoqu; Fan, Youjun; Qi, Jiuhui; Yang, Bo; Rong, Chuyan; Chen, Wei; Sun, Shigang
Abstract: Deep eutectic solvents are promising in the green synthesis of advanced functional materials owing to their several distinct advantages including good solubility, wide electrochemical window, high conductivity, low cost, nontoxicity and tolerance to humidity. Herein, we report a novel green protocol to design the hybrid PtCu nanoclusters on multi-walled carbon nanotubes in deep eutectic solvents medium without adding any surface controlling agent. Subsequently, the structure, elemental composition and electrocatalytic aspects of the as-synthesized nanohybrids are characterized by transmission electron microscopy, X-ray diffraction analysis, X-ray photoelectron spectroscopic features and electrochemical investigations. Typically, the synthesis medium plays a key role to control the dispersion of Pt-based nanoparticles and to enhance the electronic transfer interaction among the catalytic nanoparticles and support material. On other hand, the addition of alloyed Cu not only further decreases the crystallite size of catalytic particles but also results in the formation of cluster nanostructure with the coarse surface. Moreover, the methanol oxidation electrocatalytic activity of the as-fabricated material is clearly composition dependent, their maximum mass activity (Pt/Cu mass ratio 1:0.25) is about 2.5 times that of the carbon nanotubes-supported monometallic Pt catalyst. And it also presents the good CO-tolerance ability and evident long-term electrochemical durability. This study suggests that the synthesis strategy in deep eutectic solvents is of great importance to design and fabricate the high-performance electrocatalysts for fuel cells applications.